ANALYSIS OF COSTS OF DRUG USE IN TREATMENT AT THONG NHAT HOSPITAL IN 2024 - Văn Lâm, Lê; Thị Hoa, Võ; Ngọc Cẩm Tiên, Phùng; Thị Thanh Trúc, Nguyễn; Thị Hà, Trương; Thị Ngọc Thùy, Nguyễn; Thị Phương Mai, Trần; Thị Thu Hiền, Phạm (Journal of Health and Aging, 2025)
This study was conducted to analyze drug expenditure in treatment at Thống Nhất Hospital in 2024. A retrospective cross-sectional descriptive study analyzing drug usage costs in treatment at Thống Nhất Hospital in 2024. In 2024, Thống Nhất Hospital provided medical examination and treatment services to 650,000 health insurance patients, with over 595,000 outpatient visits, accounting for 90.63%. The total drug expenditure was VND 490.89 billion, representing 36.98% of the total health insurance medical examination and treatment costs. Western medicines accounted for 97.32% of the drug costs, while herbal and traditional medicines made up 2.86%. Imported drugs constituted 76.2% of the total drug expenditure. Original brand-name drugs, Group 1, and Group 2 drugs were the highest-cost categories, accounting for 38.63%, 25.59%, and 13.11% respectively. Cardiovascular drugs and those affecting the endocrine system and hormones were the most utilized, comprising 35.61% and 22.0% respectively. According to the ABC/VEN analysis, essential drugs classified as ‘E’ were the most used in terms of both quantity and cost, accounting for 58.55% and 75.51% respectively. Drug groups such as AV, AE, AN, BV, and CV represented 84.72% of the total drug expenditure. The CN group accounted for only 0.87% of the total drug expenditure in 2024. The study results indicate that the drug formulary used at Thống Nhất Hospital in 2024 aligns with the hospital’s disease patterns. The diverse and comprehensive drug list meets the treatment needs of patients.
Keywords: Thống Nhất Hospital; Drug Formulary; Drug Groups; ABC; VEN